Effectiveness of Antibiotic Use in Pediatric Diarrheal Patients Inpatient Bhina Bhakti Husada Rembang Hospital - Eko Retnowati; Puput Syah Inta Purnama; Bintari Tri Sukoharjanti; Nura Ali Dahbul (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to analyze the characteristics of pediatric inpatients with diarrhea and to evaluate the relationship between the type of antibiotics used and therapeutic effectiveness at Bhina Bhakti Husada Rembang Hospital. It was hypothesized that differences in antibiotic type might influence treatment effectiveness, although other clinical factors could also contribute. Research Method: This study used a descriptive-analytic design with a retrospective approach based on medical records of 106 pediatric inpatients diagnosed with diarrhea during June–December 2025. Data included age, sex, antibiotic type, length of hospital stay, and diarrhea frequency before and after therapy. Therapeutic effectiveness was assessed based on length of hospitalization, with ≤3 days categorized as effective and >3 days as ineffective, supported by improvement in diarrhea frequency. Data were analyzed descriptively and bivariately. Results and Discussion: Most patients were aged 1–5 years (54.7%) and male (67.9%). Nitroimidazole was the most frequently used antibiotic (53.8%), followed by third-generation cephalosporins (34.0%). Overall, 57.5% of patients were categorized as effective and 42.5% as ineffective. No significant relationship was found between antibiotic type and therapeutic effectiveness. Implications: These findings suggest that treatment success in pediatric diarrhea is multifactorial and not solely determined by antibiotic class. Further research should include disease severity, hydration status, nutritional condition, and local resistance patterns.